IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS PENEMUAN UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF PADA SISWA SMP - Khoirul Fikri Firmansyah; Hasan Subekti (PENSA: E-JURNAL PENDIDIKAN SAINS, 2023)
This research aimed to describe the implementation of learning while improving cognitive learning outcomes used discovery-based learning models and student responses. This research used pre-experimental with one group pretest and posttest design. The participants in this study were 25 students of class VII SMP. The data were collected by observation, tests, and surveys and then was analyzed quantitatively and descriptively. The results that were obtained showed the value of implementing learning included in the very good criteria. The results of the N-Gain obtained a moderate improvement category so that students' cognitive learning outcomes experienced a significant increase. The results that were analyzed of student responses to discovery-based learning showed positive responses by students with the acquisition of very good criteria. Based on these results, it can be concluded that there was an effect of discovery-based learning on cognitive learning outcomes and positive responses by seventh-grade junior high school students.